Cooling of ambient-loaded citrus in refrigerated containers: What impacts do packaging and loading temperature have?. (January 2021) - Berry, T.M.; Defraeye, T.; Wu, W.; Sibiya, M.G.; North, J.; Cronje, P.J.R.
Abstract : South Africa is the second-largest exporter of fresh citrus fruit, which is shipped to various distant markets for extended durations. Rising production quantities and increasingly more stringent phytosanitary requirements have placed considerable pressure on the logistics chain and the availability of precooling facilities. One solution to this challenge has been the application of ambient loading when using high-cube refrigerated containers, whereby fruit are cooled in-transit during shipping, instead of on-site by precooling. This study explored the effect of two package designs and the benefits of first partially precooling fruit prior to loading in shipping containers. Performance parameters was evaluated based on cooling rate and cooling uniformity of fruit within the spatial domain of the container. Containers loaded with Supervent and Opentop cartons had a mean cooling period (from initial to 4 °C) of 2.0 and 1.6 days, respectively. However, the study identified a high variability in cooling rate between and within individual containers. This was attributed to the presence of unpredictable gaps around the pallet stacks, which are formed during loading. These unique ensembles of gaps substantially influenced how cooling airflow was delivered throughout the container. The results thus showed package design is not a primary influencer of cooling performance. Partially precooling fruit to 10 °C, before loading, reduced susceptibility to chilling injury and decreased the presence of hot spots throughout the containers, so reducing the cooling variability within the shipment. This work highlighted the complex thermodynamic processes within fully loaded refrigerated containers, which should be characterised in future research. Graphical abstract: Image 1 Highlights: Partially precooling fruit reduced the presence of hot spots in containers. Unique cooling patterns observed independent of packaging type. Decay and shelf-life unaffected by the loading temperatures. Results indicate reduced chilling injury when loading at lower temperatures. Explored implications of loading configuration on cooling variability.